Magnolia x soulangiana 'Cupcake' 'Cupcake' Saucer Magnolia - Edward Gilman (EDIS)
This document provides an overview of the ‘Cupcake’ saucer magnolia (Magnolia x soulangiana ‘Cupcake’). It describes the tree’s growth habits, blooming period, and ornamental features, including its large, light pink and white flowers. The document also covers the tree’s planting requirements, hardiness zones, and potential uses in landscaping. Additionally, it highlights the tree’s moderate growth rate, pest resistance, and maintenance needs, emphasizing its suitability as a specimen plant in sunny or partially shaded spots. Original publication date October 1999.